Competitive funding and structures for public health research in European countries - McCarthy, Mark (2013)
The European Union is giving increasing emphasis to research as a driver for innovation and economic development. The European collaborative study PHIRE (Public Health Innovation and Research in Europe) investigated the funding and structures of public health research at national level in European countries.